THE CONTINUING PROFESSIONAL DEVELOPMENT OF TEACHERS FOR SCHOOLS’ INOVATIVE TEACHING METHODS - M. Velikova (Trakia Journal of Sciences)
The professional development of teachers is necessary not only to meets the standards of job realization, but also to improve their activities in response to changes in pedagogical science and practice. This report presents the results of the research project "Current status and trends for the application of innovative methods in school’s activities" durring the National Program "Young Scientists and Postdoctoral Students" in 2019. The aim of the study is to indicate the teachers’ attitude to the application of innovative teaching methods in their practice in school.